THE ROLE OF THE GOVERNMENT OF TANJUNG PINANG TO THE REACTIVITY OF TOURISM IN THE ERA OF PANDEMIC COVID-19 - Adha Putra Ritonga, Rizki (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aimed to analyze the application of health protocols to tourism activities in Tanjung Pinang City. Companies in the tourism sector, according to PHRI data (Association of Indonesian Hotels and Restaurants) for local tourism companies, there are 17 companies have approximately 10 to 15 employees. The method of this study was using the Slovin formula. The result showed that tourism employees were able to develop their abilities by attending seminars or network training to improve their abilities and increase work motivation so that the company's performance was getting better.